Serum and synovial fluid concentrations of cold‐inducible RNA‐binding protein in patients with rheumatoid arthritis. (17th June 2016) - Yoo, In Seol; Lee, Sun Young; Park, Chan Keol; Lee, Jeong Chan; Kim, Young; Yoo, Su Jin; Shim, Seung Cheol; Choi, Yoon Seok; Lee, Young; Kang, Seong Wook
Abstract: Aim: There is growing evidence that cold‐inducible RNA‐binding protein (CIRP) promotes inflammatory responses. This study investigated the relationship between CIRP and rheumatoid arthritis (RA). Methods: Peripheral blood and synovial fluid were collected from 15 patients with RA and from 16 patients with osteoarthritis (OA). The concentration of CIRP was measured with the sandwich enzyme‐linked immunosorbent assay (ELISA). Results: The concentration of serum CIRP was significantly elevated in the RA patient group (RA patients = 26.39 ± 10.48 pg/mL, OA patients = 17.14 ± 7.24 pg/mL, P = 0.009). Furthermore, the RA patient group had a significantly higher CIRP concentration than that of the OA patient group in synovial fluid (153.56 ± 108.93 pg/mL vs . 23.63 ± 16.18 pg/mL, P < 0.001). The mean synovial fluid concentration of CIRP was significantly higher than that of the serum concentration in the RA patient group (serum concentration = 26.39 ± 10.48 pg/mL, synovial fluid = 153.56 ± 108.93 pg/mL, P < 0.001). Disease Activity Score of 28 joints (DAS28)‐ESR (erythrocyte sedimentation rate) and DAS28‐CRP (C‐reactive protein) were positively correlated with the synovial fluid concentration of CIRP (DAS28‐ESR: r = 0.582, P = 0.023; DAS28‐CRP: r = 0.541, P = 0.037). Conclusion: The serum and synovial concentrations of CIRP in the RA patients were increased compared to the OA patients. Additionally, the synovial concentration of CIRP in RA patients correlated well with disease activity, that is, the DAS28‐ESR/CRP. Based on these results, CIRP mediates inflammation and is a potential marker for synovial inflammation.